α-/β-Glucosidase and α-Amylase Inhibitory Activities of Roselle (Hibiscus sabdariffa L.) Ethanol Extract - Gondokesumo, Marisca Evalina; Kusuma, Hanna Sari Widya; Widowati, Wahyu (Molecular and Cellular Biomedical Sciences, 2017)
Background: Diabetes mellitus is a metabolic disease, characterized by hyperglycemia due to disturbance in both insulin secretion and function. One of theurapeutic approaches is to reduce blood glucose levels by inhbiting α-/β-glucosidase and α-amylase involved in carbohydrate digestion. Thus, inhibition of these enzymes play important role in the treatment of diabetes mellitus. Roselle (Hibiscus sabdariffa L.) has been known to have several medicinal properties and potency as an antidiabetics agents. This reseacrh aimed to observe antidiabetic properties of roselle ethanol extract (REE) towards α-glucosidase, β-glucosidase and α-amylase.Materials and Methods: REE was done with maceration technique using diluent of 70% ethanol. Antidiabetic properties were measured by inhibitory activity of α-amylase, α-glucosidase and β-glucosidase.Results: REE was able to inhibit α-/β-glucosidase and α-amylase in the highest concentration with inhibition percentage of 72.68, 47.34 and 73.08% respectively, and were comparable with Acarbose of 81.49, 50.97, 73.08%. The median inhibitory concentration (IC50) of α-/β-glucosidase and α-amylase of REE were 15.81, 41.77, 18.09 μg/mL respectively, and Acarbose were 9.45, 22.57, 3.64 μg/mL respectively.Conclusions: REE inhibits α-/β-glucosidase and α-amylase.Keywords: Roselle, Acarbose, α-glucosidase, β-glucosidase, α-amylase, antidiabetic